2017
DOI: 10.1177/1071100717718131
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Return to Sport After Achilles Tendon Repair in National Football League Players

Abstract: Level III, retrospective comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 25 publications
3
54
1
2
Order By: Relevance
“…This is similar to a study by Jack et al in which 64% of NFL players underwent Achilles tendon repair surgery during the off-season training camps 10. Other studies have further supported this finding as significantly more injuries occurred during the first weeks of off-season training camp compared with the final weeks, with the severity of injuries decreasing as the training camp progressed 26 27.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is similar to a study by Jack et al in which 64% of NFL players underwent Achilles tendon repair surgery during the off-season training camps 10. Other studies have further supported this finding as significantly more injuries occurred during the first weeks of off-season training camp compared with the final weeks, with the severity of injuries decreasing as the training camp progressed 26 27.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have demonstrated that Achilles tendon injuries are associated with increased BMI 24. A study of the NFL by Jack et al found that defensive linemen, linebackers and offensive linemen, who have the highest BMI among NFL players, had the highest incidence of Achilles tendon repair surgeries 10. Interestingly, the defenders with the most number of Achilles tendon repairs in this study had a lower BMI (23.9±1.0 kg/m 2 ) compared with non-defenders (25.2±2.3 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Football attracts detailed media attention and public websites can provide robust data 12 13. Data from the public website transfermarkt have been used to assess the return to sport and performance after anterior cruciate ligament (ACL) injuries,14 15 fractures16 and femoro-acetabular impingement17 in professional football (soccer) players.…”
Section: Introductionmentioning
confidence: 99%
“…Amerikan Futbol Ligi'ndeki futbolcularda Aşil tendon cerrahisi sonrası lige dönüş oranı %75'ten az olarak bulunmuştur. [22] Spora dönüşü yürüyüş ve yüklenmedeki biyomekanik değişiklikler sonrası gelişen diz problemleri, karşı taraf Aşil tendinopatisi veya rüptürü (%6) gibi ek kas-iskelet sistemi patolojileri de etkileyebilmektedir. [16,23] Şekil 3.…”
Section: Spora Dönüş (24-52 Hafta)unclassified